SISTEM KEAMANAN JARINGAN KOMPUTER MENGGUNAKAN SNORT - Denny Wijanarko (Jurnal Teknologi Informasi dan Terapan, 2019)
Network security is an aspect that is always enhanced by the network administrator, the efforts both by optimizing hardware or software. Snort is a detection sensor against abuse on the network, this system functioned as a snort NIDS (Network intrusion Detection System), which works to detect any attempted intrusion (intrusions). The detection is done based on the rule that has been described by the administrator in the directory rule contained in the configuration file. Snort will analyze every packet and can record every activity performed on a network and report them if there is a potential intrusion on the network. Merging snort with SMS gateway can make the system more responsive to the potential for abuse, the log of alerts will be forwarded to the admin via SMS media, so that administrators can determine the condition of the managed network.